Killer yeasts as biocontrol agents of spoilage yeasts and bacteria isolated from wine - Fernandez de Ullivarri, Miguel (2014)
During the winemaking process Saccharomyces cerevisiae is the main yeast species but other yeasts called non-Saccharomyces as well as different species of lactic acid bacteria (LAB) are also present. Then, one strategy to prevent or reduce microbial contamination during the winemaking process is the use of killer yeasts. The aim of this study was to evaluate the killer activity (KA) of autochthonous yeasts from Northwest region of Argentine (S. cerevisiae Cf8 and Wickerhamomyces anomalus Cf20) on spoilage yeasts and in LAB of the wine. The KA was evaluated using cell-free supernatants obtained from pure and mixed cultures of strains Cf8-Cf20. S. cerevisiae Cf8 showed a growth reduction between 7 and 48% on D. anomala BDa15, P. membranifaciens BPm481 and Z. bailii Bzb317 while W. anomalus Cf20 exhibited KA of 20, 61, 91 and 92% against B. bruxellensis Ld1, D. anomala BDa15, P. membranifaciens BPm481 and P. guilliermondii Cd6, respectively. Killer mixed supernatants showed growth inhibition similar to strain Cf20. Screening against LAB showed that both killer toxins were able to inhibit the growth of L. hilgardii 5w as well as to reduce a 16–31% histamine production by this LAB strain. These results confirm the potential of autochthonous killer yeasts as biocontrol agents in winemaking process. The mixed culture S. cerevisiae Cf8-W. anomalus Cf20 presented a wide range of KA on spoilage yeasts as well as on L. hilgardii. Therefore, the use of killer yeasts as starter cultures would allow producing wines with controlled quality.